Is the activation of the postsynaptic ligand gated glycine- or GABAA receptors essential for the receptor clustering at inhibitory synapses? - Kiss, Eva; Kirsch, Joachim; Kuhse, Jochen; Kins, Stefan (Biomedicines, 2025)
One major challenge in cellular neuroscience is to elucidate how the accurate alignment of presynaptic release sites with postsynaptic densely cluster...
Das letzte A in GABAA ist tiefgestellt
Online veröffentlicht: 5. August 2025
Gesehen am 17.12.2025